2010
DOI: 10.1211/jpp.62.07.0014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of KATP openers on the QT prolongation induced by HERG-blocking drugs in guinea-pigs

Abstract: Objectives This work evaluated the potential usefulness of pharmacological activation of cardiac ATP-sensitive potassium channels (KATP) in the prevention of drug-induced QT prolongation in anaesthetised guinea-pigs. Prolongation of cardiac repolarisation and QT interval is an adverse effect of many drugs blocking HERG potassium channels. This alteration can be dangerously arrhythmogenic and has been associated with the development of a particular form of ventricular tachyarrhythmia known as torsade de pointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…One of these, NS1643, supressed dofetilide-induced QT prolongation and TdP in a rabbit model [45]. Activators of cardiac ATPsensitive potassium channels (K ATP ) such as pinacidil and cromakalim have also had beneficial effects for aLQTS associated with some but not all culprit drugs [46]. α 2 -adrenoceptor agonists attenuate L-type calcium channels and supress EADs.…”
mentioning
confidence: 99%
“…One of these, NS1643, supressed dofetilide-induced QT prolongation and TdP in a rabbit model [45]. Activators of cardiac ATPsensitive potassium channels (K ATP ) such as pinacidil and cromakalim have also had beneficial effects for aLQTS associated with some but not all culprit drugs [46]. α 2 -adrenoceptor agonists attenuate L-type calcium channels and supress EADs.…”
mentioning
confidence: 99%
“…The QTc interval was 240±3 ms, 247±10 ms and 254±5 ms immediately following amidarone administration and increased to 272±17, 279±14 and 284±14 ms following 40 min in 18, 36 and 54 mg/kg amiodarone groups, respectively (all P<0.05), which demonstrated a significant difference when compared with the normal saline group 40 min following amidarone administration (246±4 ms) in these groups (all P<0.05). The data demonstrated that the mechanism underlying the prolongation of QTc intervals induced by terfenadine and amiodarone was similar, since terfenadine as well as amiodarone are blockers of the K + channel encoded by the human ether-à-go-go-related gene (hERG) (23,24).…”
Section: Resultsmentioning
confidence: 92%
“…Implications from preclinical SQTS studies for the therapeutic deployment of K + channel activators There has been interest in the development and potential use of K + channel activators as novel antiarrhythmic agents, particularly in the setting of pathologically prolonged repolarization, where deployment of a K + channel activator may act to normalize repolarization [108][109][110]. The presence of endogenous K ATP channels comprised of K ir 6.x and SUR2A subunits, which only conduct significant current when cellular ATP falls, may exert some protective effects for the heart in situations of cardiac ischaemia or hypoxia, although it can lead to AP triangulation and associated arrhythmia risk [109,111].…”
Section: Insights From Preclinical Sqts Studies Into Arrhythmia Substmentioning
confidence: 99%